Oral fenofibrate in neonatal hyperbilirubinemia: A randomized controlled trial - Chaudhary, G S; Chaudhary, Vidya; Chaurasiya, Om Shankar; Chandrakant, Verma; Kumar, Vipin (Indian Journal of Child Health, 2016)
Objective: To evaluate the role of oral fenofibrate for lowering neonatal hyperbilirubinemia as compared to placebo. Design: Doubleblind, randomized, placebo-controlled trial. Setting: NICU of tertiary care hospital of North India. Subjects: 50 neonates with neonatal hyperbilirubinemia. Neonates (?35 weeks of gestation), birth weight (1.5-3.5 kg), jaundice beginning at day 3-11 after birth, total bilirubin level between 15 and 21 mg/dl, and clinically stable vital signs. Intervention: Neonates were assigned randomly to receive either single dose of oral fenofibrate at 10 mg/kg/dose on day 1 of admission and distilled water on the following next day or a single dose of oral glucose solution on day 1 and distilled water on the following next day. Malloy-Evelyn method was used to estimate the serum total bilirubin levels. All newborns enrolled in this study, received phototherapy. The cases were divided into two groups, i.e. study (fenofibrate) group and control group. Measurement of Primary Outcome: Duration of phototherapy. Results: Mean values for total serum bilirubin in fenofibrate group at 36 and 48 h after starting of phototherapy were significantly lower in the study group than those in the control group (p<0.00001). The mean time needed for phototherapy was also shorter in the study group than control group (p<0.0002). No side effects of fenofibrate were observed after a single dose administration. Conclusion: Fenofibrate appears to be an effective and safe drug for the treatment of neonatal hyperbilirubinemia. This decreases the duration of phototherapy and thus shortens the length of hospital stay.